Laparoscopic Sleeve Gastrectomy, with or without Staple Line Reinforcement (Medico Legal Update, 2021)
Background: Overweight and obesity are defined as abnormal or excessive fat accumulation that presentsa risk to health. A crude population measure of obesity is the body mass index. The surgical treatmentof morbid obesity is termed bariatric surgery, Laparoscopic sleeve gastrectomy first described by Gagner.Specific complications have been reported, including staple-line bleeding and staple-line leaks, Staple linereinforcement is extensively debated and highly recommended by most surgeons in an attempt to reducepostoperative complication.Aim of the Study: To compare the early complication of sleeve gastrectomy with or without staple linereinforcement by over-sewing.Patients and Method: Prospective study from 1st January 2013 to 31st January 2015, four or five ports usedaccording to surgeon preference but all of them used graduated cartridge size, some of them used to reinforce the staple line by Prolin or Vicryl and others did not. The patient was follow up for one month aftersurgery by direct contact with the surgical team.Conclusion: there was no statistically difference in the incidence of leak or bleeding in cases of sleevegastrectomy with or without staple–line reinforcement by over sewing.